Discrimination in the Macedonian multiethnic society: perceptions of inequality among the student population - Hristova, Lidija; Cekikj, Aneta (My University, 2014)
One of the fundamental problems of the multicultural societies is the feeling of marginalization and even exclusion of minority groups from society, which is closely linked with a motivation for political mobilization and action. Therefore, the goal of the presented research is to find out how the student population from different ethnic origins in the R. Macedonia experience discrimination. More specifically, the paper seeks to identify the prevalence of discrimination, to identify the spheres of life in which such discrimination is most present and the categories of citizens who are privileged or marginalized in our society. There is awareness of a widespread discrimination in Macedonian society in the most important areas of life. The bases for discrimination are numerous (ethnicity, social status, as well as friends and connections), where political affiliation is the most important factor for privileged treatment in society. The differences in perceptions between ethnic Macedonians and ethnic Albanians are in the ranking of the grounds for discrimination. However, party-political affiliation is a factor of impact for which there is the greatest concurrence of opinions and views between the two ethnic groups. When it comes to ethnicity, ethnic Albanians rank it higher than ethnic Macedonians in all areas of life examined that is in line with the main assumption of this research based on the phenomenon of the so-called minority effect.
Keywords: perception of discrimination, student population, Republic of Macedonia, ethnic discrimination, political discrimination